A photoinduced cleavage of DNA useful for determining T residues. - Simoncsits, A (1982)
Irradiation of 5'-[32P]-phosphate labeled DNA fragments with ultraviolet light in the presence of primary amines followed by piperidine treatment resulted in base-specific cleavage of the DNA chain at T residues, accompanied by a less intensive G reaction. This simple, T greater than G cleavage offers an alternative method for determining T residues in chemical DNA sequencing.